The Influence of Digital Payment Implementation on Banking Stability in Indonesia (A Study on Conventional Banks in Indonesia Listed on the Indonesia Stock Exchange) - Wahyu Taskaro, Dwi; Suhari, Endang (International Journal of Science, Technology & Management, 2024)
This study aims to investigate the influence of digital payments on the stability of conventional banks listed on the Indonesia Stock Exchange (IDX). Additionally, the research will delve into the role of banking asset quality and liquidity as control variables that may regulate the relationship between digital payments and financial stability. In examining the relationship between digital payments for MSMEs and financial system stability within the conventional banking system listed on the IDX from 2012 to 2022, the research begins by measuring digital payments and banking system stability. Sampling is conducted using purposive sampling, resulting in a collection of 27 conventional banks. The data analysis method for this research includes descriptive analysis, instrument tests, classical assumption tests, t-tests, F-tests, and hypothesis testing using multiple regression analysis. The research findings indicate that ZScore, return on assets, and return on equity have a positive effect on the stability of conventional banks in Indonesia, using Non-Performing Loans and Loan to Deposit Ratio as control variables. Thus, this study supports and strengthens previous research.